Subliminal Advertising: Ethical and Legal Problems of Existence in Ukraine - Kyrylenko, Mariia (Journal of Legal Studies, 2021)
In the present article, the issue of identification of sophisticated and problematic aspects of the regulation of subliminal advertising in the national legislation of Ukraine and perspectives for the improvement of the legal regulation of subliminal advertising is considered. It is determined that legislative and normative regulation of public relations that arise in the process of defining the concept of subliminal advertising and the problems of such legislative regulation are urgent questions in the current society. Given that subliminal advertising affects subconsciousness and manipulates human behavior, it harms not only consumers of advertising, as it misleads, disorients, has a subliminal effect, but also deprives media outlets of adequate payment for fair advertising. Besides, hidden advertising also harms society by ignoring the laws, requirements of journalistic ethics and hence – provides demoralization. That is why there is a necessity to analyze ambiguous aspects of subliminal advertising and justify the need to improve the possibilities of its legal limitations and control.